DEVELOPMENT OF SCRAPBOOK VISUAL MEDIA AS AN EFFORT TO INTRODUCE SEX EDUCATION TO CHILDREN AGED 4-5 YEARS - Islamiya, Suwaibatul; Eka Oktavianingsih, (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2024)
This research was motivated by the lack of understanding of children aged 4-5 years at RA Mabdaus Sholah about sex education and the limited learning media to introduce sex education. This study aims to develop visual scrapbook media to introduce sex education and determine the feasibility of visual scrapbook media in introducing sex education for children aged 4-5 years. This research is included in the type of Research and Development (R&D) research using the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. Data collection techniques consist of interviews, questionnaires, observation and documentation. The test subjects consisted of 22 children who were divided into small group trials of 6 children and large group trials of 16 children. The results obtained are based on the percentage of each of them, namely material experts of 85.7%, media experts of 95.5%, children's responses in small group trials of 89.6%, children's responses in large group trials of 92% and the results are included in the Very Feasible category. Based on the results of the study, it can be concluded that visual scrapbook media as an effort to introduce sex education in children aged 4-5 years is feasible to use as learning media so that the use of visual scrapbook media can make it easier for children to understand sex education material. Suggestions for further research are to develop other visual media that can be used to introduce sex education to early childhood.